A topic-based synchronisation protocol in peer-to-peer publish/subscribe systems. (8th November 2019) - Nakamura, Shigenari; Enokido, Tomoya; Takizawa, Makoto
In this paper, we discuss a peer-to-peer type of publish/subscribe (P2PPS) model which is composed of peer processes (peers). Here, each peer publishes event messages while receiving event messages. In the topic-based access control (TBAC) model proposed in our previous studies, only a peer granted publication and subscription rights on topics is allowed to publish and subscribe event messages on the topics, respectively. In our previous studies, the subscription-based synchronisation (SBS) protocol is proposed where illegal event messages are banned. It is checked whether or not each event message received is illegal in terms of subscription and publication rights granted to each peer. However, even some legal event messages are unnecessarily banned. In this paper, we newly propose a topic-based synchronisation (TBS) protocol where only and every illegal event message is banned. In the evaluation, we show only and every illegal event message is banned in the TBS protocol.